Five new species of the long-legged sac spider genus Cheiracanthium C.L. Koch, 1839 (Araneae: Cheiracanthiidae) from China - Li, Zhaoyi; Zhang, Feng (European Journal of Taxonomy, 2023)
Five species of the cheiracanthiid spider genus Cheiracanthium C.L. Koch, 1839 collected from China are diagnosed and described as new to science based on morphological characters: Cheiracanthium arcilongum sp. nov. (♂♀) from Yunnan, C. circulum sp. nov. (♂♀) from Yunnan, C. digitatum sp. nov. (♂♀) from Anhui, C. jiuquan sp. nov. (♂♀) from Guangxi and C. xinjiangense sp. nov. (♂♀) from Xinjiang. In addition, the photos of the habitus, copulatory organs and distribution map are provided for all species. However, DNA barcodes information is only provided for four species.